Inspection and gaging - Kennedy, Clifford ([S.l.] : Industrial Press, Inc., 1987)
Concise yet comprehensive, this highly acclaimed training manual and reference provides the many phases of inspection work and their application to today's manufacturing operations through a practical down-to-earth presentation. Discusses a range of manual and automatic measuring devices along with their specific functions and the specialized functions involved in their use. Analyzes the methods and duties of inspectors. Appropriate for use by inspection supervisors, plant managers, quality control engineers and subcontractors. Includes SPC and other data analysis methods for manufacturing applications. Provides detailed discussions of available measuring and quantitative systems. Compares important measuring and gaging systems.